(untitled) (Experimental biology, 2018)
In the article presents data on the population of small mammals in the industrial zone of Pavlodar for the summer period 2016-2017. Analyzed of the main structural indicators of the diversity of communities of small mammals, as bioindicators of the condition of ecosystems in zones of technogenic load, in comparison with the control sites. During the period of research in the compared territories, we recorded 19 species of small mammals. In the zone of technogenic load 15 were recorded, and 13 species in the control area, and simultaneously in two territories nine common species of small mammals were registered. The technogenic territory is dominated mainly by two species - the narrow-skulled vole and the southern birch mouse. In the control area, the narrow-skulled vole predominates, as well as the tundra shrew, the pigmy shrew and the common shrew, and also the harvest mouse. Interpopulation variability of morphometric exterior characteristics of a narrow-skulled vole was investigated. The analysis showed a regular decrease in the size indices of body length and weight of animals in the territories of technogenic load. The areas of technogenic load zones are subject to strong anthropogenic transformations of landscapes and to a significant change and fragmentation of habitats, ultimately affecting on the dynamics and stability of the population the narrow-skulled vole. As a result, many animals lose their ability to the migrate and to populate suitable border habitats, forming local populations.